Some peace of mind: assessing a pilot intervention to promote mental health among widows of injecting drug users in north-east India - Dzuvichu Bernice; Chandra Prabha; Devine Alexandra; Kermode Michelle; Gilbert Thomhood; Herrman Helen (BMC, 2008)
Abstract Background HIV prevalence in north-east India is high and injecting drug use (IDU) is common. Due to HIV-related deaths there are increasing numbers of IDU widows, many of whom are HIV infected, and experiencing poor health, social isolation, discrimination and poverty, all factors likely to be compromising their mental health. There is increasing recognition of the links between HIV and mental health. Methods The aim of this study was to pilot a peer-facilitated, participatory action group (PAG) process and assess the impact of the intervention on the mental health of participants. The intervention consisted of 10 PAG meetings involving 74 IDU widows. Changes in quality of life (WHOQOL-BREF), mental health (GHQ12) and somatic symptoms were assessed. The value of the intervention from the perspective of the participants was captured using a qualitative evaluation method (Most Significant Change). Results Participants' quality of life, mental health and experience of somatic symptoms improved significantly over the course of the intervention, and the women told stories reflecting a range of 'significant changes'. Conclusion This pilot intervention study demonstrated that a participatory approach to mental health promotion can have a positive impact on the lives of vulnerable women, and the potential to contribute to HIV prevention. Further investigation is warranted.